Human blood biomarkers for glioma and meningioma detection by a portable visible resonance Raman analyzer - Zhang, Liang; Zhou, Yan; Zhang, Shengjia; Wu, Binlin; Zhu, Ke; Zhang, Chunyuan; Liu, Cheng-hui; Yu, Xinguang; Alfano, Robert R. (Optical biopsy XIX: Toward real-time spectroscopic imaging and diagnosis, 2021)
Recent reports pointed out that the application of optical spectroscopy in the field of liquid biopsy has aroused great interest among researchers and demonstrated the potential of its clinical application. We report a preliminary investigation on the visible resonance Raman (VRR) spectra of human brain blood liquid collected from the scalp and around the meningeal tumor during surgery and a set of venous blood samples from healthy people and glioma grade III patients using a portable VRR-LRRTM, HR800, HR-Evolution and WITec300 Raman systems in vivo and ex vivo. The biochemical fingerprints and molecular biomarkers were found. These findings indicate that if VRR spectroscopy technology is combined with polymerase chain reaction (PCR) or genetic molecular biomarker methods (VRR-PCR), it will greatly increase the possibility for its clinical application. © 2021 SPIE.
1 citations (Crossref) [2023-10-31]
Keywords: Biomarkers; Biopsy; Blood; Clinical application; Healthy people; Molecular biomarker; Optical spectroscopy; Polymerase chain reaction; Raman systems; Resonance Raman; Spectroscopy; Spectroscopy technology; Tumors; Venous bloods; dept.phy